French reportive comme clauses: A case of parenthetical adjunction - Desmets, Marianne; Roussarie, Laurent (The Proceedings of the 7th International Conference on Head-Driven Phrase Structure Grammar, 2001)
In this paper, we present a surface-based analysis of a specific type of French parenthetical adjunct clauses introduced by the adverb comme (similar to as in English). The construction we focus on belongs to the domain of reported speech, and we call it reportive-comme clause (RCC). The set of data we consider exhibits a large amount of notable properties that can only be fully explained under the assumption of constructional constraints. Therefore, following Sag (1997) and Abeillé et al. (1998), we base our approach on the central notion of "construction". We claim that RCCs are adverbial extraction contexts. We integrate them in a cross-classified typed hierarchy as a subtype of relative clauses, and a subtype of head-adjunct and head-filler phrases. Semantic specifications of RCCs are expressed with constraints on different levels. We draw a general distinction between head-modifier adjuncts and parenthetical adjuncts in order to account for the fact that parenthetical adjuncts do not contribute the referential content of the head phrase they selected for. We posit two subtypes of RCCs determined by a Direct speech (and quotative) vs. Indirect speech distribution of properties. The two sets of defining constraints allow to characterize the restricted classes of verbs possible in the different RCCs, the syntactic realization (gap or pronominal affix) of their object argument and its anaphoric semantics. This treatment constitutes a more general proposal for direct speech or quoted argument selection, which is known as a puzzling problem of the syntax-semantic interface. It innovates in presenting a formalized account of reported speech phenomena and present a typed-based classification of the semantic relations of reported speech predicates.